The Role Of The Lurah In The Community Empowerment Program As An Effort To Realize Sustainable Development Goals (Sdgs) In Berangas Sub-District, Alalak Barito Kuala District - Erna Suriyani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This study aims to find out the role of the lurah in community empowerment as an effort to realize the Sustainable Development Goals (SDGs) in Berangas Village, Alalak District, Barito Kuala Regency, and want to know the obstacles faced in community empowerment. The type of research used is descriptive research with a qualitative approach. Data collection was done by interview, observation and documentation. The role of the lurah is seen from its role as a motivator, facilitator, regulator and mobilizer. The research findings revealed that the role of the lurah in community empowerment was not maximized, especially in the role of facilitator. Constraints faced are limited budget, mindset or mindset of the community and the reduced potential of natural resources, and very limited community self-help. It is recommended that there be sufficient financial support, empowerment models and collaboration with other agencies or universities as supporters of community empowerment programs.